Customary law as an instrument of restorative justice: an alternative approach to criminal conflict resolution in plural legal systems - Rahmi Dwi Sutanti; Pujiyono; Nur Rochaeti; Arsyad Rifki Damora (Clío)
As a pluralistic nation, Indonesia recognizes the importance of customary law, as guaranteed in Article 28I of its Constitution. This study explores the application of customary law in criminal conflict resolution through a restorative justice approach. To illustrate this, the research focuses on the Megou Pak Tulang Bawang Indigenous Community in Lampung, which serves as a representative case study of how local wisdom is implemented within a broader, universally relevant legal framework. Utilizing an empirical juridical method, the study draws on primary data from interviews with traditional leaders and secondary data from literature and legal documents. The findings indicate that criminal cases within the Megou Pak community are resolved through a customary trial process known as Peppung, which prioritizes reconciliation between the offender and the victim. Sanctions—both material and symbolic—are imposed to restore social and cosmic harmony. Once both parties agree on the resolution, a ritual called Angkon Muakhi or Mewari is performed, symbolically integrating the victim into the offender’s family to reestablish peaceful relations. This process is rooted in the local philosophy of Piil Pesenggiri, which upholds the values of responsibility, mutual cooperation, and deliberative consensus. The study concludes that customary law in the Megou Pak community exemplifies a form of restorative justice that addresses the limitations of the formal criminal justice system. It offers an effective alternative dispute resolution model that is culturally embedded, socially responsive, and aligned with the broader goals of the national legal system. Therefore, customary law should be acknowledged and integrated as a vital element within Indonesia’s national legal framework.